LANDASAN FILOSOFIS DAN MAQĀṢID SYARĪ‘AH DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) - Miwaldi Amriza; Aria Putra; Sukimun Sukimun; Sandy Jayusman Isnur; Sri Wahyuni (Ensiklopedia of Journal, 2026)
The development of an Islamic Religious Education (PAI) curriculum requires a strong conceptual foundation to address the challenges of social and cultural change and scientific development. This article aims to analyze the philosophical foundation and Maqāṣid Syarī‘ah (the principles of Islamic law) in Islamic Religious Education curriculum development and examine their integration within the context of contemporary Islamic education. This research uses a qualitative approach with a literature review of scientific literature published in the last five years. The results indicate that the philosophical foundation provides ontological, epistemological, and axiological direction in Islamic Religious Education curriculum development, while Maqāṣid Syarī‘ah serves as a value framework oriented toward the well-being of students. The integration of the two results in an Islamic Religious Education curriculum that is holistic, contextual, and oriented toward character development, critical thinking, and social responsibility. Thus, the Islamic Religious Education curriculum is expected to emphasize not only the cognitive aspects of religion but also sustainably shape students' moral and social awareness.Keywords: Philosophical Foundation, Maqāṣid Syarī‘ah, Islamic Religious Education Curriculum, Islamic Education